A Generalizability Analysis of the Meaning in Life Questionnaire for Chinese Adolescents - Wei Chen (Frontiers Media S.A., 2021)
The level of meaning in life not only affects the physical health of individuals, but also is closely related to their mental health. At present, many self-reported questionnaires are being used to measure the meaning in life of Chinese adolescents. Using the multivariate generalizability theory, this study investigated the psychometric properties and the internal structure of the Meaning in Life Questionnaires (MLQs), the most widely used questionnaire for assessing the level of meaning in life of Chinese adolescents. The data were sample of 1,951 junior high school students from Guizhou, China. Multivariate random measurement mode p × i° is the primary analytic approach. Results showed that the generalizability coefficient and dependability index of the scale were 0.86 and 0.85, respectively. The generalizability coefficients of presence of meaning and search for meaning were 0.76 and 0.85, respectively, and the dependability indexes were 0.75 and 0.85 for MLQ-P and MLQ-S, respectively. The design of each factor for MLQ is reasonable in terms of score ratio and the number of projects. In brief, the reliability and factor structure of the scale are satisfactory.